The effect of different hyperglucagonemic states on monooxygenase activities and isozymic pattern of cytochrome P-450 in mouse. Issue 4 (April 1985) - Rouer, E.; Beaune, P.; Augereau, C.; Leroux, J. P.
Abstract : The continuous infusion of a low dose of glucagon (35 μg/kg/d, for 5 d) constitutes, in view of glucose-6-phosphatase and phosphoenolpyruvate carboxykinase activities, a reliable experimental model of hyperglucagonemia. By conjunction of monooxygenase assays and immunoquantitation of specific isozymes of cytochrome P-450, the actual inducing ability of glucagon has been shown and it might explain some of the modifications of the drug metabolizing system in diabetic mice. The isozymic pattern of cytochrome P-430 of liver microsomes from diabetic mice appears very different from that produced by classical inducers.